2018
DOI: 10.3389/fpsyg.2018.00528
|View full text |Cite
|
Sign up to set email alerts
|

Seeing More Than Human: Autism and Anthropomorphic Theory of Mind

Abstract: Theory of mind (ToM) is defined as the process of taking another’s perspective. Anthropomorphism can be seen as the extension of ToM to non-human entities. This review examines the literature concerning ToM and anthropomorphism in relation to individuals with Autism Spectrum Disorder (ASD), specifically addressing the questions of how and why those on the spectrum both show an increased interest for anthropomorphism and may even show improved ToM abilities when judging the mental states of anthropomorphic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 172 publications
3
50
1
Order By: Relevance
“…Interaction with nonhuman agents may be experienced as more comfortable compared with human interaction due to various reasons, such as their level of predictability, 1 controllability, and lower social and sensory complexity. 20 Third, participants in both groups described experiencing concern and feelings of sympathy and empathy toward agents, in line with previous studies indicating that anthropomorphism predicts moral concern for anthropomorphized agents. 12,13 Previous accounts have proposed that autistic individuals are lacking in cognitive empathy, 40 possibly due to poor introspective ability and a lack of self-other distinction, 41 yet autistic participants in the current study described extensive empathic responses to nonhuman agents.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Interaction with nonhuman agents may be experienced as more comfortable compared with human interaction due to various reasons, such as their level of predictability, 1 controllability, and lower social and sensory complexity. 20 Third, participants in both groups described experiencing concern and feelings of sympathy and empathy toward agents, in line with previous studies indicating that anthropomorphism predicts moral concern for anthropomorphized agents. 12,13 Previous accounts have proposed that autistic individuals are lacking in cognitive empathy, 40 possibly due to poor introspective ability and a lack of self-other distinction, 41 yet autistic participants in the current study described extensive empathic responses to nonhuman agents.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, a recent review suggested anthropomorphic tendencies among autistic individuals may be motivated by the considerable difference in the complexity of interaction with humans compared with nonhuman agents. 20 An alternative account is that, for autistic people, anthropomorphism may be linked to synesthesia (a condition in which certain stimuli trigger unusual, automatic, and involuntary sensations). Recently, subtypes of social synesthesia are identified, in which individuals attribute gender, feelings, and personality traits to graphemes and/or inanimate objects, in a manner that is consistent over time.…”
Section: Introductionmentioning
confidence: 99%
“…It is not unusual for people to "see human" in the non-human; indeed it is a robust human tendency thought to underlie common religious practices and possibly the human-animal bond (Epley, Waytz, Akalis, & Cacioppo, 2008). While autistic people have been shown to perform poorly on some tests measuring anthropomorphic tendencies (Klin, 2000), a recent review on this topic highlights how autistic people may actually show an increased affinity for both anthropomorphizing and understanding anthropomorphic agents (Atherton & Cross, 2018). In particular, it is suggested that the ToM deficits sometimes found in this population might be ameliorated when mentalizing about human-like rather than human entities (Brosnan, Johnson, Grawmeyer, Chapman, & Benton, 2015;Rosset et al, 2008;Whyte, Behrmann, Minshew, Garcia, & Scherf, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Mentalizing would create possibilities for individual interactions with God-images, which could induce effects on social functioning among schizophrenia patients [15,49]. Perhaps our patients, similarly to individuals with autism spectrum disorders, have distinctive processes of taking another's perspective when incoming stimuli are only human-like rather than human [50], and can process them with fewer emotional risks.…”
Section: Discussionmentioning
confidence: 99%